2019
DOI: 10.1111/jcmm.14507
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis identified core signal pathways and hypoxic characteristics of human glioblastoma

Abstract: As a hallmark for glioblastoma (GBM), high heterogeneity causes a variety of phenotypes and therapeutic responses among GBM patients, and it contributes to treatment failure. Moreover, hypoxia is a predominant feature of GBM and contributes greatly to its phenotype. To analyse the landscape of gene expression and hypoxic characteristics of GBM cells and their clinical significance in GBM patients, we performed transcriptome analysis of the GBM cell line U87‐MG and the normal glial cell line HEB under normoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…TIMP-1 has both MMPs-dependent anti-proteolytic activity and MMP-independent cell growth activity [ 23 ]. Our results show that TIMP1 promotes the occurrence and development of GC, which is consistent with previous reports about TIMP1 as an oncogene in other cancers, including breast cancer [ 24 ], colon cancer [ 10 ], glioblastoma [ 25 ], and non-small cell lung cancer [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…TIMP-1 has both MMPs-dependent anti-proteolytic activity and MMP-independent cell growth activity [ 23 ]. Our results show that TIMP1 promotes the occurrence and development of GC, which is consistent with previous reports about TIMP1 as an oncogene in other cancers, including breast cancer [ 24 ], colon cancer [ 10 ], glioblastoma [ 25 ], and non-small cell lung cancer [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…For example, in pancreatic ductal adenocarcinoma (PDA) and head and neck squamous cell carcinoma (HNSCC), inflammasomes of tumor-associated macrophages activate caspase-1 and mediate the cleavage of GSDMD and the release of mature IL1 β , resulting in the suppression of CD8+ T cells [ 13 , 14 ]. Although inflammasome-mediated pyroptosis in glioma has not been reported, IL1 β has been shown to be a serum marker in glioblastoma [ 16 , 17 ], which prompted us to explore potential pyroptosis pathways in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…As an important molecular marker of pyroptosis [9], IL1β is generally released from the pore formed by oligomerized GSDMD [12] and has been shown to be closely associated with the formation of an immunosuppressive microenvironment in several tumor types [13][14][15]. Notably, several studies have shown that the proinflammatory cytokine IL1β is significantly elevated in the serum of glioblastoma (GBM) patients and serves as a potential serum marker for this type of disease [16,17]. In addition, a very recent study showed that monocyte-derived macrophages in gliomas secrete IL1β in response to tumor cell induction, while Il1b knockdown significantly prolonged the survival time of primary glioma mice [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thioredoxin-interacting protein ( TXNIP ) was reported as a tumor-suppressor gene in glioma ( Zhang et al, 2017 ). VIM had been identified as a potential biopsy marker for glioma in several bioinformatics analyses ( Gao et al, 2019 ; Wang J. J. et al, 2021 ; Herrera-Oropeza et al, 2021 ). Also, our results corroborated these analyses.…”
Section: Discussionmentioning
confidence: 99%